Analysis of Regional Balance in East Java Province - Nuriyatul Inayatil Yaqinah (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2025)
One of the goals of development is equity, balance, and justice. This study aims to analyze the regional balance in East Java Province. Using a quantitative approach, this study analyzes development disparities between regions in East Java province. The data used include indicators of regional balance from various districts or cities in East Java and see the relationship between the dependent variable Percentage of Poor Population and the independent variables Regional Minimum Wage (RMW), Human Development Index (HDI), Gross Regional Domestic Product (GRDP), and Open Unemployment Rate (OUR). The analysis method used is the primacy index to measure regional imbalance. The results showed that simultaneously, RMW, HDI, GRDP, and OUR have a significant effect on the percentage of poor people. At the same time, partially, there is a substantial effect of RMW on the percentage of poor people, there is a significant effect of HDI on the percentage of poor people, there is no significant effect of GRDP on the percentage of poor people, and there is no significant effect of OUR on the percentage of poor people.